2020
DOI: 10.3389/fonc.2020.563731
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Prediction Value of Systemic Inflammation Score and the Development of a Nomogram for Patients With Surgically Treated Breast Cancer

Abstract: Background: Systemic inflammation score (SIS) has been verified as a novel prognostic indicator in several cancer types. However, its prognostic value in breast cancer remains unknown. Furthermore, a nomogram based on SIS is yet to be constructed for breast cancer. We conducted this study to explore the association between SIS and prognosis of breast cancer, and to construct a good prognostic nomogram model. Methods: A total of 1,180 breast cancer patients who underwent curative surgery between December 2010 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
(40 reference statements)
0
17
0
Order By: Relevance
“… 11 , 37 As mediators of inflammatory response, inflammatory cells play a very important part in tumor microenvironment (TME), 36 and circulating inflammatory-nutritional biomarkers, including PLR, NLR, MLR, CONUT, SIS, SIRI, SII, and AAPR, are significantly associated with survival and have been considered as independent predictors for breast cancer patients. 16–18 , 21 , 23 , 26 Over the past few years, optimal predictors or prognostic models based on one or a few inflammatory-nutritional biomarkers for women with breast cancer have been explored extensively, but they have limited clinical value because the weight values of individual inflammatory biomarkers to the risk score are not equal. For example, a high NLR is usually considered as an indicator of a poor prognosis, 19 , 38 but NLR failed to show independent value in the multivariate Cox analysis in other studies when identifying patients with a pathological complete response or achievement of disease-free status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 11 , 37 As mediators of inflammatory response, inflammatory cells play a very important part in tumor microenvironment (TME), 36 and circulating inflammatory-nutritional biomarkers, including PLR, NLR, MLR, CONUT, SIS, SIRI, SII, and AAPR, are significantly associated with survival and have been considered as independent predictors for breast cancer patients. 16–18 , 21 , 23 , 26 Over the past few years, optimal predictors or prognostic models based on one or a few inflammatory-nutritional biomarkers for women with breast cancer have been explored extensively, but they have limited clinical value because the weight values of individual inflammatory biomarkers to the risk score are not equal. For example, a high NLR is usually considered as an indicator of a poor prognosis, 19 , 38 but NLR failed to show independent value in the multivariate Cox analysis in other studies when identifying patients with a pathological complete response or achievement of disease-free status.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of multiple biomarkers could provide prognostic models with substantially higher predictive accuracy than that achieved with models based on one or a few inflammatory biomarkers. 12 , 21 , 37 But most of current studies simply combined candidate inflammatory parameters with strong collinearity and correlation into a multivariate Cox regression model to identify independent predictors, which can lead to conflict between parameters and certain statistical problems. 12 In this study, we performed the LASSO Cox regression analysis to include the maximal number of available inflammatory-nutritional biomarkers and effectively single out four valuable inflammatory indexes, namely, NLR, MLR, PNI, and AAPR; this approach could avoid the influence of multicollinearity to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the prognostic models that included blood markers, Cho et al conducted a small sample study and only verified the role of PLR, but failed to include important factors that have been confirmed, such as LMR, NLR, NMR and ALB [ 31 ]. Huang et al reported that the systemic inflammation score (SIS) based on ALB and LMR could predict the survival of breast cancer patients [ 32 ]. Zheng et al found that fibrinogen-albumin ratio and platelet-lymphocyte ratio score was a prognostic factor of breast cancer [ 33 ], and NLR has been shown to predict the efficacy of neoadjuvant chemotherapy in breast cancer [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%